in, of Res Ipsa Loquitur Doctrine in Proofing Process of Environmental Dispute - Janeman Jehezkiel Lanawaang (Fakultas Hukum Universitas Hang Tuah, 2020)
The purpose of this study is to discover the philosophy of accountability in environmental disputes and discover the legal rationality of the validity of the Res Ipsa Loquitur doctrine in resolving environmental disputes in Indonesia. The results of the study show that 1) The philosophy of accountability in environmental disputes is the human right because of the existence of human beings as conscientious, intelligent, conscious and free beings who use their conscience, reason, awareness and freedom (ontologism) where their fulfillment is based on moral legislation (epistemological) to bring about justice, legal certainty and expediency (axiological) and 2) The rationality of the legality of the doctrine of res ipsa loquitur is in the environmental dispute is first, the difficulty of proving mistakes (intentional or negligence) in environmental disputes; Second, reversing the burden of proof still requires proof of innocence and causality between loss and mistakes; The three absolute responsibilities still require proof from the defendant regarding the loss caused; Fourth, the allegation evidence still requires the support of other evidence, so that a mechanism for resolving environmental disputes in favor of the environment (novio pro natura) is needed without proof of the mistakes, losses and causality of both but sufficient with the fact of environmental damage that is located in the power of the defendant so the allegation that arises is presumption by factuality with a form of responsibility to compensate absolutely (absolutely compentation liability).